Green synthesis of 3D cesium lead halide perovskite nanocrystals and 2D Ruddlesden–Popper nanoplatelets in menthol-based deep eutectic solvents. (30th January 2023) - Chatterjee, Shovon; Sen, Arghya; Sen, Pratik
Abstract : To overcome organic solvent hazards, deep eutectic solvents have been employed for the synthesis of cesium lead halide perovskite nanocrystals/nanoplatelets. Abstract : Organic solvent hazards are the most overlooked part of perovskite research. In this report, we employed menthol based deep eutectic solvents (DESs) as a green medium for the synthesis of cesium lead halide (CsPbX3 ; X = Cl, Br, I, or either both) nanocrystals (NCs) and nanoplates (NPLs) with high PLQY (maximum of 78%) aiming to reduce the synthesis related toxicity. The reaction temperature and added precursor ratio in the DES medium were found to be the key factor in controlling the dimensionality of the NCs. The synthesized NCs and NPLs in the DES medium suffer from common halide vacancy-related defects, which were passivated by oleylammonium halide treatment to achieve near unity PLQY. With green DES as a synthesis medium, the present synthetic protocol lowered the crystallization temperature, allowing ambient condition synthesis, and yields high quality NCs/NPLs with an almost uniform size distribution. This study presents a novel approach to the environmentally friendly synthesis of NCs and NPLs, which holds great potential for the practical large-scale synthesis of perovskites in industrial settings.